2018
DOI: 10.1093/jrr/rry008
|View full text |Cite
|
Sign up to set email alerts
|

Present developments in reaching an international consensus for a model-based approach to particle beam therapy

Abstract: Particle beam therapy (PBT), including proton and carbon ion therapy, is an emerging innovative treatment for cancer patients. Due to the high cost of and limited access to treatment, meticulous selection of patients who would benefit most from PBT, when compared with standard X-ray therapy (XRT), is necessary. Due to the cost and labor involved in randomized controlled trials, the model-based approach (MBA) is used as an alternative means of establishing scientific evidence in medicine, and it can be improved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Of these, two thirds evaluated DDose rather than DNTCP. This might be explained by the lack of high quality NTCP-models for several tumour types [32]. The model-based approach has been adopted in the Netherlands, Denmark, France, Germany, Italy, and Spain for a number of tumour sites including GI, breast and HNC.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, two thirds evaluated DDose rather than DNTCP. This might be explained by the lack of high quality NTCP-models for several tumour types [32]. The model-based approach has been adopted in the Netherlands, Denmark, France, Germany, Italy, and Spain for a number of tumour sites including GI, breast and HNC.…”
Section: Discussionmentioning
confidence: 99%
“…The NTCP model is a valuable tool to translate the dosimetric advantage of IMPT into a clinical benefit. The NTCP model-based approach has been used as a strategy to select patients who will potentially benefit from PBT [32] , [33] , [34] . Our results confirmed the clinical benefit of IMPT because there was a significant reduction in NTCP for the heart and lungs, which was consistent with previous studies [11] , [25] .…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously shown that NTCP models developed for photon therapy did retain discriminatory properties for proton therapy and could hence be used to select patients [ 60 ]. Furthermore, the conformality afforded by proton therapy decreases concerns such that an NTCP model can reliably score a radiation plan for both photons and protons [ 61 , 62 ].…”
Section: Methodsmentioning
confidence: 99%